تأثير كفاءة قراءة كتاب التراث في تحسين مهارة الكلام لطلاب الصف التاسع بمعهد سبيل الرشاد الإسلامية مالانج - QA, Nur; Syarofah, Alfiatus (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2024)
ABSTRACT The ability to read the yellow book is one of the most things to develop Arabic Language Skills. The process of learning the yellow book has an influence in improving students' speaking skills. Wich one is learning nahwu and sharaf with the yellow book and the question and the answer process during the learning process. Thus, researchers see an effect on fluency in speaking and whether or not the rules of nahwu and sharaf are correct in students during the learning process in class or when speaking in Arabic. The aims of this study were: (1) To find out how the process of learning the yellow book at Sabilurrosyad Islamic Boarding School Malang. (2) To find out how much effect the ability of the yellow book in improving the speaking skills of grade nine students of Sabiluurrosyad Islamic Boarding School Malang. This study uses a quantitative approach and experimental method with the type of Pre-Experimental Designs. The data collection methods in this study were observation, tests (pre-test and post-test), and documentation. The results of this study are: (1) Learning to Read the Yellow Book at Sabilurrosyad Islamic Boarding School Using the Jurumiyah Reading Module Book with the learning process of the teacher reading and explaining the material first then students appreciate, understand and reread with other books that have not been harokati in front of the subject teacher read the book. (2) The ability to read the yellow book can improve students' speaking skills. These results were obtained from observations in experimental classes, student activity was quite high, namely 80% and teacher activity 78%, Improvement in Speaking Skills due to ineffective learning of the yellow book in grade nine students of Sablurrosyad Islamic Boarding School Malang. Based on the average result of the experimental class, which is 36% based on the N-Gain score. The results of the t-test obtained a significant value = 0.000 smaller than 0.005 thus H1 is accepted and H0 is rejected. ملخص كفاءة كتاب التراث من أهم الأشياء المهمة لتطوير مهارة اللغة العربية. عملية تعلمية قراءة كتاب التراث لها تأثير في تحسين مهارة الكلام الطلاب. من بعض هو تعليم نحوو وصرف في قراءة كتاب التراث وعملية الأسئلة والأجوبة أثناء عملية التعلمية. قامت يرى الباحثة تأثير الطلاقة كانت كلام بفصيح و قواعد نحوو وصرف أثناء عملية التعلمية في الفصل أو عند الكلام باللغة العربية. أهداف هذا البحث هي: (1) لمعرفة كيف عملية تعليمة قراءة كتاب التراث في سبيل الرشاد معهد الإسلامية مالانج. (2) لمعرفة ما مدى تأثير كفاءة قراءة كتاب التراث في تحسين قدرة مهارة الكلام لطلاب الصف التاسع بمعهد سبيل الرشاد الإسلامية مالانج. استخدمت الباحثة في هذا البحث مدخل الكمي بمنهج تجربي في تصاميم ما قبل التجريبية. وأما طريقة جمع البيانات في هذا البحث هي الملاحظة، التوثيق و الاختبارات (الاختبار القبلي والبعدي). نتائج هذا البحث هي: (1) تعليم قراءة كتاب التراث في معهد سبيل الرشاد بمالانج استخدم كتاب وحدة القراءة الجرومية مع عملية التعلمية يقرأ المعلم ويشرح المادة أولا ثم يقدر الطلاب ويفهمون ويعيدون قراءتها مع الكتاب الأخرى التي لم يتم حركة أمام معلم المادة قراءة الكتاب. (2) كفاءة قراءة كتاب التراث تحسين مهارة الكلام لطلاب. تم الحصول على هذه النتائج من نتائج الملاحظة في الفصل التجريبي وحصلت الطلاب نتائج عالية الطلاب أي 80% والمدرس 78%، تحسين مهارة الكلام بسبب كفاءة الكتاب التراث لدى طلاب الصف التاسع في معهد الإسلامة الحكومية سبيل الرشاد مالانج غير فعالة. بناء على متوسط نتيجة الفصل التجريبي، وهو 36٪ بناء على درجة N-Gain. وحصلت نتائج اختبار t على قيمة معنوية = 0.000 أصغر من 0.05، بحيث تم H1 مقبول وتم H0 مرفوض.